Effect of displacement on livelihood activities of rural dwellers within omo forest reserve of Ogun state, Nigeria (2014)
The study assessed the effect of displacement on livelihood activities of the rural dwellers within Omo Forest Reserve in Ogun State. Multistage sampling procedure was used to select 108 respondents. Data on livelihood activities, sources of information, effect of displacement on livelihood activities as well as constraints faced by respondents due to displacement with respect to livelihood activities were collected through structured interview schedule. Frequency counts, percentages, Chi-square, PPMC and t-test were used to analyze the data. Results reveal that most (67.5%) of the respondents were below 50 years, married (58.5%), males (72.8%) and 89.8% had educational level up to secondary school. Little above half (53.7%) were indigenes and 97.2% had experienced displacement thrice or less. Change in government policies was regarded as the major cause (89.9%) of the displacement. Displacement reduces both cash and arable crop production most and the effect was high on majority (68.5%) of the respondents. Major constraints to involvement in livelihood activities were transportation (ẋ=2.98) and fear of untimely displacement (ẋ=2.89). There were significant relationships between marital status (χ2=18.454), years of formal education (χ2=18.659), effect of livelihood activities (r=- 0.460,); causes of displacement (r=-0.460); constraint to involvement (r=-0.329) and level of involvement in livelihood activities. Displacement had negative implications on the respondents’ livelihood activities. It is recommended that participatory and sustainable approaches that would resolve displacement issues should be designed so as to prevent conflict and disruption of livelihood.